The Credibility Gap: Why 68% of Marketers Reject Superior AI Reports (200-CMO Blind Test) - Dzreke, Simon; Dzreke, Semefa Elikplim (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: A significant paradox undercuts artificial intelligence's promise in strategic marketing: while 92% of organizations already use AI-generated insights, 74% of executives distrust them for crucial decisions. Research Design and Methodology: This study addresses the credibility dilemma by conducting a groundbreaking blind test with 200 Chief Marketing Officers from Fortune 500 companies, analyzing identical business challenges—half answered by premier AI platforms (GPT-4 and custom LLMs), and half by experienced human analysts. Findings and Discussion: The technique found an unexpected discrepancy: whereas NLP assessment indicated AI matched or exceeded human report quality in 82% of cases, displaying higher predictive accuracy (+14%) and data comprehensiveness, executives rejected 68% of algorithmically generated insights. A multivariate study identified explanatory inadequacies as the crucial factor: AI's inability to communicate why patterns mattered (causal reasoning), base discoveries in operational realities (contextual framing), and structure insights coherently (narrative flow) accounted for 53% of the trust gap. This